The Moscow Art Theatre - Worrall, Nick (Taylor & Francis, 1996)
Unprecedented in its comprehensiveness, The Moscow Art Theatre fills a large gap in our knowledge of Stanislavsky and his theatre. Worrall focuses in particular detail on four of The Moscow Art Theatre's best-known productions.